Fundamental physics with ESPRESSO - da Fonseca, Vítor (2022)
This work was financed by FEDER–Fundo Europeu de Desenvolvimento Regional funds through the COMPETE 2020–Operational Programme for Competitiveness and Internationalisation (POCI), and by Portuguese funds through FCT – Fundação para a Ciência e a Tecnologia under projects POCI-01-0145-FEDER-028987. MTM acknowledges the support of the Australian Research Council through Future Fellowship grant FT180100194. The INAF authors acknowledge financial support of the Italian Ministry of Education, University, and Research with PRIN 201278X4FL and the “Progetti Premiali” funding scheme. TMS also acknowledges the support from the Swiss National Science Foundation (SNSF) and the University of Geneva. M-RZO acknowledges funding under project PID2019-109522GB-C51 of the Spanish Ministerio de Ciencia e Investigación. ASM and JIGH acknowledge financial support from the Spanish Ministry of Science and Innovation (MICIN) project PID2020-117493GB-I00. ASM also acknowledges financial support from the Spanish Ministry of Science and Innovation (MICINN) under 2018 Juan de la Cierva program IJC2018-035229-I, as well as from the Government of the Canary Islands project ProID2020010129. Publisher Copyright: ©